STATE AND PROSPECTS OF THE DEVELOPMENT OF PUBLIC DIPLOMACY IN UKRAINE DURING THE LARGE-SCALE RUSSIAN-UKRAINIAN WAR - ZAIETS, Dmytro (Fìlosofìâ ta polìtologìâ v kontekstì sučasnoï kulʹturi, 2024)
The article examines approaches to understanding public diplomacy and the potential of «soft power». A brief overview of modern types of public diplomacy, in particular cultural and digital, is given, and the peculiarities of cultural diplomacy are revealed. The article highlights that in modern political science, several approaches to the study of public diplomacy and its components can be distinguished. They are due to the emergence of the concepts of «soft power», «smart power», «national branding», as well as the close interdisciplinary interaction of public diplomacy, political science, sociology, marketing, public relations and information technologies.It is noted that currently a lot of attention is paid to the use of public diplomacy in the implementation of foreign policy programs of the countries of the world, which is connected with the strengthening of the role of civil society: residents of different countries receive more tools to influence the institutions of power both in their country and abroad. Communication channels (both new and traditional) are gaining more and more importance, changing the formats and methods of working with the population of foreign countries. The increase in the number of military conflicts inevitably forces interested states to look for new forms of influence on the foreign public and to review current programs in the field of diplomacy.The problems of public diplomacy of Ukraine, the relationship between the concepts of «public diplomacy» and «propaganda» are considered.The current state of public diplomacy, as well as the peculiarities of its implementation during the Russian-Ukrainian war, are studied. Emphasis is placed on the conditions under which public diplomacy in Ukraine has to be implemented at the present time. It was noted that in the conditions of Russian aggression, public diplomacy of Ukraine became a profitable direction of conducting foreign policy thanks to the third wave of globalization, as a result of which the society finally moved from an industrial to an informational state. The main vectors of the development of public diplomacy of Ukraine are considered.